2007
DOI: 10.2169/internalmedicine.46.0331
|View full text |Cite
|
Sign up to set email alerts
|

Primary Peripheral Adenoid Cystic Carcinoma of the Lung and Literature Comparison of Features

Abstract: Adenoid cystic carcinoma arising from the peripheral lung is rare. Here, we describe adenoid cystic carcinoma that developed in the peripherally in S 9 of the right lower lobe of an 84-year-old woman. Cell blocks prepared from the bronchial wash specimens exhibited the cribriform formation. An immunohistochemical examination of the surgically resected tumor revealed positive thyroid transcription factor-1 and c-kit staining. Exons 9 and 11 of c-kit in tumor cells were not mutated. We compared the clinical feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
6
1
Order By: Relevance
“…Peripheral lung ACC is represents approximately 10% of primary lung ACC. Peripheral lung ACC arises from bronchi smaller than the segmental bronchus which are named as lobular and terminal bronchi [3,7]. Our presented case is rather different from those presented in previous reports.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Peripheral lung ACC is represents approximately 10% of primary lung ACC. Peripheral lung ACC arises from bronchi smaller than the segmental bronchus which are named as lobular and terminal bronchi [3,7]. Our presented case is rather different from those presented in previous reports.…”
Section: Discussioncontrasting
confidence: 76%
“…Additionally they are found in 79% of the fifth order bronchi (as named lobulary bronchi), but in only 11% of the sixth order bronchi (as named terminal bronchi) [4]. Therefore, primary pulmonary ACC is commonly arise from central extra-pulmonary airways such as trachea and main bronchus [2,3]. Peripheral lung ACC is represents approximately 10% of primary lung ACC.…”
Section: Discussionmentioning
confidence: 99%
“…Yokouchi et al reviewed the English literature and found 10 cases of ACC. They reported that males were more frequently affected than females, although ACC was more frequent among women in a larger study in which the average patient age was 58 years and two of 10 patients developed recurrence (one case of lung metastasis and one case of lymph node metastasis) after surgery [19]. Although no recurrence was observed for two postoperative years in the present case, recurrence was detected after nine years; therefore, providing careful follow-up observation is mandatory [20].…”
Section: Discussionmentioning
confidence: 98%
“…Our cases were positive for MYB and c-KIT, consistent with ACC. Tumor cells were also positive for TTF-1, indicating that the origin was the lung [1,22,23]. In Case 1, the patient had a history of adenocarcinoma of the colon posing an additional diagnostic challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The lung ACC cells in the present study expressed TTF-1. TTF-1 is a protein expressesd in the forebrain, thyroid, and lung [24] and only a few reports [1,22,23] have described the expression of TTF-1 in primary lung ACC.…”
Section: Discussionmentioning
confidence: 99%